Dentists’ Role in Diagnosis and Management of Oral Involvement of Nasopharyngeal Carcinoma: Serial Case Report - Kadrianto, Theodorus H.; Noegroho, Harum S. (UI Scholars Hub, 2015)
Nasopharyngeal carcinoma (NPC) is still a significant health problem due to its relatively high incidence. Rarely, NPC could extend and involve the oral cavity, and may present as an ulceration or exophytic mass. Objectives: To discuss the rare clinical appearance of NPC involving the oral cavity and the significant role of dentists in its diagnosis and management. Case Report: We reported 3 cases of NPC with oral cavity involvement. In the first two cases, the patients presented with persistent oral ulceration with bone exposure and perforation to the above structure. The third patient presented with an ulcerated exophytic mass with temporomandibular disorder. The ulceration occAurred due to bone destruction by the expansion of NPC mass, which indicated advance stage of the disease. All patients were managed with twice a day 0.2% chlorhexidine gluconate rinsing in combination with placing a chlorhexidine-moistened gauze to inhibit bacterial overgrowth and prevent secondary infection. The use of chlorhexidine was substituted by saline solution during patients’ radiotherapy and chemotherapy cycles. Conclusion: Dentist’s awareness to recognize the oral cavity involvement of NPC as well as recognizing the symptoms of NPC is very important, in order to make appropriate diagnosis and oral management. The oral management will eventually affect treatment outcome and quality of life.